Rekreasyon Deneyimi, Memnuniyet ve Çevreye Duyarlı Davranış İlişkisi: Horma Kanyonu Örneği - Akkuş, Çetin; Yordam, Selda (Muharrem TUNA, 2020)
With today’s changing and developing economic, social and environmental factors, the ways that people using their leisure time are getting differentiated. Due to this differentiation, nature-based activities have recently become highly demanded touristic products and services. Recreational experiences also play an important role in nature-based tourism. The recreational experience associated with nature-based tourism is a very important factor in increasing the environmentally sensitive behavior of nature-based tourists. For the sustainable resource continuity and environmental quality, environmentally responsible behavior of individuals is important. In this context, helping the tourist to adopt environmentally sustainable principles and raising awareness of environmental issues are among the main purposes of the experience. In this study, it is thought that the environmentally responsible behavior of tourists who have a positive recreational experience will increase. In this study, it is aimed to reveal the relationship between tourists' recreational experience, tourist satisfaction and environmentally responsible behavior. For this purpose, 310 participants among the tourists visiting the Horma Canyon in the Küre Mountains National Park of Kastamonu province were reached with the convenience sampling method and the survey technique was applied. As a result of the analyses, it has been determined that the recreation experience positively affects the tourist satisfaction and environmentally responsible behavior. Another conclusion of the study was that the tourist satisfaction assumed an intermediary role. Some suggestions were offered using the findings obtained.

Günümüzde değişen ve gelişen ekonomik, sosyal ve çevresel faktörlerle birlikte, bireylerin boş zamanını değerlendirme biçimleri farklılaşmaktadır. Bu farklılaşmadan kaynaklı olarak doğa temelli aktiviteler son zamanlarda oldukça talep gören turistik ürün ve hizmetler haline gelmiştir. Rekreasyon deneyimleri de doğa temelli turizmde önemli bir rol oynamaktadır. Doğa temelli turizm ile ilişkili rekreasyon deneyimi, doğa temelli turistlerin çevreye duyarlı davranışlarını artırmak için çok önemli bir faktördür. Sürdürülebilir kaynak devamlılığı ve çevre kalitesi için bireylerin çevreye duyarlı davranışı önem arz etmektedir. Bu bağlamda, turistin çevresel olarak sürdürülebilir ilkeleri benimsemesine yardımcı olmak ve çevreyle ilgili konularda farkındalığını artırmak deneyimin ana amaçları arasında yer almaktadır. Yapılan bu çalışmada olumlu yönde rekreasyon deneyimi yaşayan turistlerin çevreye duyarlı davranışının da artacağı düşünülmektedir. Bu araştırmada turistlerin rekreasyon deneyimi, turist memnuniyeti ve çevreye duyarlı davranış ilişkisini ortaya koymak amaçlanmaktadır. Bu amaç doğrultusunda Kastamonu ili Küre Dağları Milli Parkı içerisinde yer alan Horma Kanyonu’nu ziyaret eden turistler arasında kolayda örnekleme yöntemiyle 310 katılımcıya ulaşılmış ve anket tekniği uygulanmıştır. Analizler neticesinde rekreasyon deneyiminin turist memnuniyeti ve çevreye duyarlı davranışı olumlu yönde etkilediği tespit edilmiştir. Ayrıca turist memnuniyetinin aracılık rolü üstlendiği çalışmanın bir diğer sonucunu oluşturmuştur. Elde edilen bulgulardan yararlanılarak birtakım öneriler sunulmuştur.
Keywords: Turizm (Diğer); Tourism (Other); Rekreasyon Deneyimi; Memnuniyet; Çevreye Duyarlı Davranış; Horma Kanyonu; Recreation Experience; Satisfaction; Environmentally Responsible Behavior; 13. Climate action; 11. Sustainability; 12. Responsible consumption